Emotional Regulation Among Postgraduate Students - Shati, Prof.Dr. Abdul Abbas Ghadhib; Nasser, Zainab Abdul Redha (Thi Qar Arts Journal, 2024)
The current research aims to identify the emotional regulation among postgraduate students and the significance of differences in emotional regulation according to the variables of gender (male - female) and specialization (scientific - humanities). The researchers prepared an emotional regulation scale consisting of (24) items distributed over five domains (situation selection, situation modification, cognitive change, attention deployment, response modulation). The research was conducted on a sample of (277) male and female students at the University of Dhi Qar. The items of the scale were statistically analyzed to calculate their discriminative ability and validity coefficients. The researchers verified the face validity and construct validity indicators of the scale and calculated the reliability coefficient (alpha - test-retest). To ensure the research procedures and results, the researchers used appropriate statistical methods. The results are as follows:• Postgraduate students possess emotional regulation.• There are no statistically significant differences according to the variables of gender (male - female) and specialization (scientific - humanities).The results were interpreted based on theory, the theoretical framework, and the results of previous studies. In light of the findings of the current research, the researchers made several recommendations and suggestions.Recommendations: The Ministry of Education should hold training workshops and specialized seminars to increase awareness of emotional regulation at all educational stages, which can enhance and stimulate strategic thinking.Suggestions: Study the correlational relationship between emotional regulation and other variables such as aggressive behavior.: